2021
DOI: 10.3390/pharmaceutics13091395
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Levodopa and 3-O-Methyldopa in Parkinsonian Patients Treated with Levodopa and Ropinirole and in Patients with Motor Complications

Urszula Adamiak-Giera,
Wojciech Jawień,
Anna Pierzchlińska
et al.

Abstract: Parkinson’s disease (PD) is a progressive, neurodegenerative disorder primarily affecting dopaminergic neuronal systems, with impaired motor function as a consequence. The most effective treatment for PD remains the administration of oral levodopa (LD). Long-term LD treatment is frequently associated with motor fluctuations and dyskinesias, which exert a serious impact on a patient’s quality of life. The aim of our study was to determine the pharmacokinetics of LD: used as monotherapy or in combination with ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Wang et al [ 17 ] proposed that ropinirole stimulates D2‐MSNs, inducing an imbalance between D1‐ and D2‐MSN‐based motor pathways, which may lead to ropinirole inducing more dyskinesia per unit of normal movement. Adamiak‐Giera et al [ 18 ] indicated that ropinirole may cause dyskinesia by influencing 3‐O‐methyldopa (3‐OMD) concentration. 3‐OMD is a major metabolite of levodopa.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 17 ] proposed that ropinirole stimulates D2‐MSNs, inducing an imbalance between D1‐ and D2‐MSN‐based motor pathways, which may lead to ropinirole inducing more dyskinesia per unit of normal movement. Adamiak‐Giera et al [ 18 ] indicated that ropinirole may cause dyskinesia by influencing 3‐O‐methyldopa (3‐OMD) concentration. 3‐OMD is a major metabolite of levodopa.…”
Section: Discussionmentioning
confidence: 99%
“…COMT is expressed in all peripheral tissues and in the central nervous system (CNS) while the peripheral component is critical for the CNS bioavailability of levodopa. Peripheral COMT not only reduces levodopa concentrations, but its product 3-OMD also competes with levodopa in terms of blood–brain barrier transport and CNS dopamine uptake, and thus worsens motor function (Wade and Katzman 1975 ; Nyholm 2006 ; Adamiak et al 2010 ; Adamiak-Giera et al 2021 ). For this reason, COMT inhibition acts not only by increasing levels of levodopa transported into the CNS, but also through a sustained reduction of its competitor 3-OMD, an effect that is potentiated upon presence of dopamine decarboxylase inhibitors (DDCI) (Bonifacio et al 2012 ).…”
Section: Comt Inhibitorsmentioning
confidence: 99%
“…Improving the adverse pharmacokinetics of levodopa is a constant challenge [15][16][17], with several alternatives widely used. Further positive effects are expected from the introduction of the new peripheral catechol-O-methyltransferase inhibitor (COMT-i) opicapone [18] and the reversible monoamine oxidase B inhibitor (MAO-Bi) and glutamate modulator safinamide [19,20].…”
Section: Discussionmentioning
confidence: 99%